2017
DOI: 10.1007/s00432-017-2540-1
|View full text |Cite
|
Sign up to set email alerts
|

Model-based optimization of G-CSF treatment during cytotoxic chemotherapy

Abstract: PurposeAlthough G-CSF is widely used to prevent or ameliorate leukopenia during cytotoxic chemotherapies, its optimal use is still under debate and depends on many therapy parameters such as dosing and timing of cytotoxic drugs and G-CSF, G-CSF pharmaceuticals used and individual risk factors of patients.MethodsWe integrate available biological knowledge and clinical data regarding cell kinetics of bone marrow granulopoiesis, the cytotoxic effects of chemotherapy and pharmacokinetics and pharmacodynamics of G-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 89 publications
0
12
0
Order By: Relevance
“…Some models have been proposed to optimise G‐CSF administration. Although pegfilgrastim, a PEGylated form of the growth factor, increases patient compliance, filgrastim appears to be more ductile, enabling its administration to be individually tailored to patients …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some models have been proposed to optimise G‐CSF administration. Although pegfilgrastim, a PEGylated form of the growth factor, increases patient compliance, filgrastim appears to be more ductile, enabling its administration to be individually tailored to patients …”
Section: Resultsmentioning
confidence: 99%
“…The authors reported that, for the highest risk group, filgrastim should begin 6‐8 days after the start of therapy, cycle with at least eight injections. Timing is less important for medium‐ and low‐risk groups, with six and four injections, respectively, obtaining sufficient neutrophil recovery …”
Section: Methodsmentioning
confidence: 99%
“…In this (still ongoing) study clinicians from different hospitals and cancer centres outside our consortium are involved as test users. The implemented models itself as well as the MAGPIE model server have already been tested and validated independently ( [1][2][3][4][5][6][7][8]12]). Although tested for model correctness and for general usability, the presented framework is still a prototype.…”
Section: Discussionmentioning
confidence: 99%
“…2 Schematic outline (screenshots) of framework components/features and information flows. Our prototype provides management of patient-identifying data (1) and corresponding medical data (2) complemented by an integrated graphical representation (3). Mathematical model predictions can be generated interactively for user-defined parameter settings (slider-based parameter selection) and visualized in comparison to the clinical data (4).…”
Section: Prediction Of Treatment-response Dynamics In CML (Use Case 1)mentioning
confidence: 99%
See 1 more Smart Citation